Oncogene-dependent survival of highly transformed cancer cells under conditions of extreme centrifugal force – implications for studies on extracellular vesicles - Lee, Tae Hoon; Chennakrishnaiah, Shilpa; Rak, Janusz (Cellular & molecular biology letters, 2015)
Extracellular vesicles (EVs), including exosomes, are a subject of intense interest due to their emission by cancer cells and role in intercellular communication. Earlier reports suggested that oncogenes, such as RAS, MET or EGFR, drive cellular vesiculation. Interestingly, these oncogenes may also traffic between cells using the EV-mediated emission and uptake processes. One of the main tools in the analysis of EVs are ultracentrifugation protocols designed to efficiently separate parental cells from vesicles through a sequence of steps involving increasing g-force. Here we report that ultracentrifugationonly EV preparations from highly transformed cancer cells, driven by the overexpression of oncogenic H-ras (RAS-3) and v-src (SRC-3), may contain clonogenic cancer cells, while preparations of normal or less aggressive human cell lines are generally free from such contamination. Introduction of a filtration step eliminates clonogenic cells from the ultracentrifugate. The survival of RAS-3 and SRC-3 cells under extreme conditions of centrifugal force (110,000 g) is oncogene-induced, as EV preparations of their parental non-tumourigenic cell line (IEC-18) contain negligible numbers of clonogenic cells. Moreover, treatment of SRC-3 cells with the SRC inhibitor (PP2) markedly reduces the presence of such cells in the unfiltered ultracentrifugate. These observations enforce the notion that EV preparations require careful filtration steps, especially in the case of material produced by highly transformed cancer cell types. We also suggest that oncogenic transformation may render cells unexpectedly resistant to extreme physical forces, which may affect their biological properties in vivo.